CHIRAL ORGANOMETALLIC NADH MIMICS - PREPARATION OF HOMOCHIRAL (R)-(-)-[(ETA-5-C5H5)FE(CO)(PPH2(O-(L)-MENTHYL))]-1-METHYL-1,4-DIHYDRONICOTINOYL AND ASYMMETRIC REDUCTION OF ETHYL BENZOYLFORMATE - Davies, S; Skerlj, R; Whittaker, M (1990)
The homochiral complex (R)-(-)-[(η5-C5H5)Fe(CO)(PPh2(O-(l)-menthyl))]-1-methyl-1,4-dihydronicotinoyl reduces ethyl benzoylformate to ethyl mandelate in 52% enantiomeric excess. © 1990.